Efficacy of Mouth Rinses Against SARS-CoV-2: A Scoping Review - Ather, Amber; Parolia, Abhishek; Ruparel, Nikita B. (Frontiers in Dental Medicine, 2021)
Introduction: The presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in saliva and nasopharyngeal secretions has challenged the routine practice of dentistry. Use of preprocedural mouth rinses has been recommended by several organizations to potentially reduce the transmission of SARS-CoV-2. This scoping review aimed at evaluating the available evidence on the efficacy of mouth rinses against SARS-CoV-2. Methods: A thorough literature search on electronic databases (PubMed, Scopus, and Google Scholar) was performed by two independent reviewers and data from articles addressing the aim of this article were extracted. Results: After exclusion of articles not addressing the end point in question, 12 articles were included in this scoping review. Of the 12 articles, seven were in vitro studies and five were in vivo human clinical studies. The in vitro studies used a standardized methodology (endpoint dilution assay) to evaluate the efficacy of antimicrobial mouth rinses against SARS-CoV-2. The in vivo studies were done utilizing polymerase chain reaction assay of samples obtained from saliva or nasopharyngeal swab or a combination of both nasopharyngeal and oropharyngeal swab. The reagents tested in these studies included povidone-iodine, chlorhexidine, hydrogen peroxide (H2O2), essential oils, and quaternary ammonium compounds and demonstrated varied efficacy against SARS-CoV-2. Conclusion: Based on the available evidence from in vitro studies, it can be concluded that mouth rinses have a potential to reduce SARS-CoV-2 viral load; however, effectiveness in in vivo conditions is still inconclusive. Owing to the substantial heterogeneity in reporting of the anti–SARS-CoV-2 efficacy of mouth rinses, this review highlights the need to conduct future research with robust and standardized methodologies to confirm effectiveness of mouth rinses.